Law as a catalyst and remedy for civic violence in early Rome : two examples from Dionysius of Halicarnassus - Stefano Carlo Sala (Cahiers des Études Anciennes)
This paper analyses the historical account of Dionysius of Halicarnassus concerning the passing of two plebeian laws, the lex Publilia Voleronis in 471 BC (D.H. A.R. 9.37-49) and the lex Icilia de Aventino publicando in 456 BC (D.H. A.R. 10.31-32). In particular, the analysis focuses on the narrative strategies adopted by Dionysius to present the eruption and resolution of violence resulting from the internal strife caused by these bill proposals. Among such strategies Dionysius privileges the characterization of the plebeian tribunes and of their opponents, the moderation of the early Romans, as well as the insertion of ideas from Greek political thought into the speeches of his characters. By adopting these strategies, Dionysius draws an idealized picture of the political development of early Rome, where moderation and the reliance on debates is contrasted with the extreme violence of the late Republic.